The ethics of workplace health promotion - Kuhn, Eva; Mueller, Sebastian; Heidbrink, Ludger; Buyx, Alena (Public Health Ethics, 2020)
Companies increasingly offer their employees the opportunity to participate in voluntary Workplace Health Promotion programmes. Although such programmes have come into focus through national and regional regulation throughout much of the Western world, their ethical implications remain largely unexamined. This article maps the territory of the ethical issues that have arisen in relation to voluntary health promotion in the workplace against the background of asymmetric relationships between employers and employees. It addresses questions of autonomy and voluntariness, discrimination and distributive justice, as well as privacy and responsibility. Following this analysis, we highlight the inadequacy of currently established ethical frameworks to sufficiently cover all aspects of workplace health promotion. Thus, we recommend the consideration of principles from all such frameworks in combination, in a joint reflection of an Ethics of Workplace Health Promotion.
CRIS-Team Scopus Importer:2023-03-08